PENERAPAN TEKNOLOGI PIROLISIS SAMPAH PLASTIK DI DESA UKO - Fatuh Rahman; Putra Putra; Eka Tefiana Fitrianti; Hudriansyah Hudriansyah; Abdullah Yahya; Primadiyanti Arsela (Jurnal Abdi Insani, 2025)
This research aims to develop a simple pyrolysis device as an alternative solution for plastic waste management in Uko Village, Muara Komam District, Paser Regency. The increasing volume of unmanaged plastic waste has caused environmental and social problems, requiring appropriate technology that can be applied at the household or community level. An experimental approach was employed by designing and testing a pyrolysis system using a pressure cooker as the reactor. The process was conducted at 325°C with 453 grams of LDPE and PS plastics. The experiment produced 195 ml of clear yellowish pyrolysis oil with a yield of approximately 43%. This oil has a calorific value comparable to diesel fuel, making it a potential alternative energy source for rural communities. Implementing this technology within a Community Service Program (PKM) in Uko Village provided dual benefits—reducing plastic waste accumulation while raising community awareness of sustainable waste management. Furthermore, the produced pyrolysis oil can be used as household fuel, reducing expenses and offering new economic opportunities. Thus, this simple pyrolysis innovation effectively supports plastic waste reduction and empowers rural communities toward a circular economy based on renewable energy.